2000
DOI: 10.1007/s007020070063
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D in schizophrenia, major depression and alcoholism

Abstract: 25-Hydroxyvitamin D3, 1,25-dihydroxyvitamin D3, calcium, phosphate and parathyreoidal hormone levels were assessed in 34 patients with schizophrenia (DSM-III-R, 44% female, mean age 38.9 +/- 2.1 years), 30 patients with alcohol addiction (16% female, mean age 48.7 +/- 2.2 years), 25 patients with major depression (56% female, mean age 57.6+/- years) and 31 healthy controls. Only 25-hydroxyvitamin D3 and 1,25-dihydroxvitamin D3 levels were significantly lower in all groups of psychiatric patients than in normal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
101
2
5

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(116 citation statements)
references
References 1 publication
8
101
2
5
Order By: Relevance
“…However, there is evidence to suggest that vitamin D among people with psychosis is correlated with the season of blood sampling (Belzeaux et al, 2015;Berg et al, 2010;Crews et al, 2013;Grønli et al, 2014;Lally et al, 2016;Zhu et al, 2015) and parathyroid hormone levels (Bergemann et al, 2008;Rey-Sánchez et al, 2009;Schneider et al, 2000), the latter being negatively correlated to vitamin D. What this review highlights are a multitude of variables that have been found to not significantly correlate with vitamin D within the patient population including but not limited to: BMI, age, gender, smoking, duration of illness and GAF score.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is evidence to suggest that vitamin D among people with psychosis is correlated with the season of blood sampling (Belzeaux et al, 2015;Berg et al, 2010;Crews et al, 2013;Grønli et al, 2014;Lally et al, 2016;Zhu et al, 2015) and parathyroid hormone levels (Bergemann et al, 2008;Rey-Sánchez et al, 2009;Schneider et al, 2000), the latter being negatively correlated to vitamin D. What this review highlights are a multitude of variables that have been found to not significantly correlate with vitamin D within the patient population including but not limited to: BMI, age, gender, smoking, duration of illness and GAF score.…”
Section: Discussionmentioning
confidence: 99%
“…Itzhaky et al 17 found in their study that hypovitaminosis D is more prominent in schizophrenic patients compared to patients with depression. Moreover, in the meta-analysis of Belvederi Murri et al 28 and in the study of Schneider et al 13 , it was found that 25(OH)D levels between these two disorders were similar. The cause of this contradiction could be attributed to the small number of samples included in the study, and to the fact that vitamin D was considered deficient at different values, and to the existing geographic and cultural variability of the patients included.…”
Section: Cmjmentioning
confidence: 93%
“…Majority of the studies in this field investigate vitamin D deficiency without focusing on the psychiatric diagnosis of psychiatric inpatients 5,10,11 . A limited number of studies attempted to compare vitamin D levels among psychiatric diagnoses 12,13 . However, such studies, relying on very small samples, offer conflicting results about the psychiatric disorder where vitamin D deficiency is prevalent.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have demonstrated that 25 (OH) D which is thought to be a more reliable marker in the determination of vitamin D levels, is at a lower concen-tration in depressive patients relative to healthy controls (Eskandari et al 2007, Hoogendijk et al 2008, Jorde et al 2006, Schneider et al 2000. However some other studies do not support these finding (Herrán et al 2000, Pan et al 2009).…”
Section: Introductionmentioning
confidence: 99%